American Society of Hematology 2020 Guidelines for Management of Venous Thromboembolism: Treatment of Deep Vein Thrombosis and Pulmonary Embolism - Ortel, Thomas L.; Neumann, Ignacio; Ageno, Walter; Beyth, Rebecca; Clark, Nathan P.; Cuker, Adam; Hutten, Barbara A.; Jaff, Michael R.; Manja, Veena; Schulman, Sam; Thurston, Caitlin; Vedantham, Suresh; et al. (Blood advances, 2020)
In August 2022, these guidelines were reviewed by an expert work group convened by ASH. Review included limited searches for new evidence and discussion of the search results. Following this review, the ASH Committee on Quality agreed to continue monitoring the supporting evidence rather than revise or retire these guidelines at this time. Limited searches and expert review will be repeated annually going forward until these guidelines are revised or retired. Background: Venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), occurs in ∼1 to 2 individuals per 1000 each year, corresponding to ∼300 000 to 600 000 events in the United States annually. Objective: These evidence-based guidelines from the American Society of Hematology (ASH) intend to support patients, clinicians, and others in decisions about treatment of VTE. Methods: ASH formed a multidisciplinary guideline panel balanced to minimize potential bias from conflicts of interest. The McMaster University GRADE Centre supported the guideline development process, including updating or performing systematic evidence reviews. The panel prioritized clinical questions and outcomes according to their importance for clinicians and adult patients. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to assess evidence and make recommendations, which were subject to public comment. Results: The panel agreed on 28 recommendations for the initial management of VTE, primary treatment, secondary prevention, and treatment of recurrent VTE events. Conclusions: Strong recommendations include the use of thrombolytic therapy for patients with PE and hemodynamic compromise, use of an international normalized ratio (INR) range of 2.0 to 3.0 over a lower INR range for patients with VTE who use a vitamin K antagonist (VKA) for secondary prevention, and use of indefinite anticoagulation for patients with recurrent unprovoked VTE. Conditional recommendations include the preference for home treatment over hospital-based treatment for uncomplicated DVT and PE at low risk for complications and a preference for direct oral anticoagulants over VKA for primary treatment of VTE.